The Metallogeny of the Tieling Cu-Mo Porphyry Deposit in Eastern Tianshan, NW China: New Insights from Zircon U-Pb, Fluid Inclusion, and H-O-S Stable Isotope Analyses. (21st September 2021) - Li, Ping; Liang, Ting; Huang, Fan; Zhao, Tongyang; Zhu, Zhixin; Li, Yong; Feng, Jing; He, Lei
Abstract : The eastern Tianshan metallogenic belt is an important molybdenum resource base in Xinjiang and is characterized by large-scale porphyry Mo deposits formed during the Triassic. The Tieling Cu-Mo porphyry deposit, which is situated in the western part of the eastern Tianshan metallogenic belt, was recently recognized as being related to Carboniferous granite porphyry. Three stages of hydrothermal mineralization were identified, including quartz+K-feldspar+pyrite±molybdenite±magnetite (stage I), quartz+molybdenite+pyrite+chalcopyrite (stage II), and quartz+pyrite±molybdenite±epidote (stage III). Fluid inclusion petrography and microthermometry analyses indicate the presence of gas-liquid inclusions with a H2 O-NaCl composition. The ore-forming fluids have a characteristic temperature ranging from 157 to 262°C under stage II and 135 to 173°C under stage III, which correspond to salinities of 7.2-17.2 wt% NaCl equiv. and 5.9 to 9.6 wt% NaCl equiv., respectively. The hydrogen and oxygen isotope data indicate that the ore-forming fluids of the Tieling deposit were originally derived from magmatic hydrothermal fluids and then mixed with meteoric water. The sulfur isotope compositions indicate that the ore-forming materials were mainly derived from the Late Carboniferous felsic magma. Furthermore, zircon U-Pb analysis of ore-bearing granite porphyry yields a concordant age of 298.4 ± 0.7   Ma, indicating that the Tieling Cu-Mo deposit formed during the Late Carboniferous and differed from that processed under pre-Early Carboniferous and Triassic mineralization in the eastern Tianshan metallogenic belt. These results also indicate that the Tieling porphyry deposit was formed in the transition condition between subduction-related accretion and postcollisional orogeny, and it should be given more attention in prospect evaluations.